Searching the veterinary literature: a comparison of the coverage of veterinary journals by nine bibliographic databases - Grindlay, Douglas J.C.; Brennan, Marnie L.; Dean, Rachel S. (University of Toronto Press, 2016)
A thorough search of the literature to find the best evidence is central to the practice of evidence-based veterinary medicine. This requires knowing which databases to search to maximize journal coverage. The aim of the present study was to compare the coverage of active veterinary journals by nine bibliographic databases to inform future systematic reviews and other evidence-based searches. Coverage was assessed using lists of included journals produced by the database providers. For 121 active veterinary journals in the “Basic List of Veterinary Medical Serials, Third Edition,” the percentage coverage was the highest for Scopus (98.3%) and CAB Abstracts (97.5%). For an extensive list of 1,139 journals with significant veterinary content compiled from a variety of sources, coverage was much greater in CAB Abstracts (90.2%) than in any other database, the next highest coverage being in Scopus (58.3%). The maximum coverage of the extensive journal list that could be obtained in a search without including CAB Abstracts was 69.8%. It was concluded that to maximize journal coverage and avoid missing potentially relevant evidence, CAB Abstracts should be included in any veterinary literature search.